Pencegahan COVID-19 Melalui Pelatihan Pembuatan Hand Sanitizer Lidah Buaya pada Ibu-Ibu Aisyiah PCM Depok secara Daring - Rachma Tia Evitasari; Gita Indah Budiarti; Endah Sulistiawati (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2021)
Abstract: Kapanewon Depok is located in the north of Yogyakarta City with rapid development. One of the groups here is the Aisyiah PCM Depok Women's Group, which is still less productive. This activity aims to increase the knowledge and skills of participants in making hand sanitizers. The method of implementing this community service activity is entirely carried out online. The implementation of the activities is divided into four stages of planning, implementation, mentoring, and evaluation. The results of the evaluation of hand sanitizer training activities showed that there was an increase in the knowledge and skills of participants in making hand sanitizers. Participants who previously only knew a little about how to make hand sanitizers, after this activity their knowledge and skills increased by 100%.